Beautiful death : Jewish poetry and martyrdom in medieval France - Einbinder, Susan L., 1954- (Jews, Christians, and Muslims from the ancient to the modern world., 2002)
When Crusader armies on their way to the Holy Land attacked Jewish communities in the Rhine Valley, many Jews chose suicide over death at the hands of Christian mobs. With their defiant deaths, the medieval Jewish martyr was born. With the literary commemoration of the victims, Jewish martyrology followed. Beautiful Death examines the evolution of a long-neglected corpus of Hebrew poetry, the laments reflecting the specific conditions of Jewish life in northern France. The poems offer insight into everyday life and into the ways medieval French Jews responded to persecution.